Endothelium‐Derived Hyperpolarization and Coronary Vasodilation: Diverse and Integrated Roles of Epoxyeicosatrienoic Acids, Hydrogen Peroxide, and Gap Junctions. (January 2016) - Ellinsworth, David C.; Sandow, Shaun L.; Shukla, Nilima; Liu, Yanping; Jeremy, Jamie Y.; Gutterman, David D.
Abstract: Myocardial perfusion and coronary vascular resistance are regulated by signaling metabolites released from the local myocardium that act either directly on the VSMC or indirectly via stimulation of the endothelium. A prominent mechanism of vasodilation is EDH of the arteriolar smooth muscle, with EETs and H2 O2 playing important roles in EDH in the coronary microcirculation. In some cases, EETs and H2 O2 are released as transferable hyperpolarizing factors (EDHFs) that act directly on the VSMCs. By contrast, EETs and H2 O2 can also promote endothelial KCa activity secondary to the amplification of extracellular Ca 2+ influx and Ca 2+ mobilization from intracellular stores, respectively. The resulting endothelial hyperpolarization may subsequently conduct to the media via myoendothelial gap junctions or potentially lead to the release of a chemically distinct factor(s). Furthermore, in human isolated coronary arterioles dilator signaling involving EETs and H2 O2 may be integrated, being either complimentary or inhibitory depending on the stimulus. With an emphasis on the human coronary microcirculation, this review addresses the diverse and integrated mechanisms by which EETs and H2 O2 regulate vessel tone and also examines the hypothesis that myoendothelial microdomain signaling facilitates EDH activity in the human heart.